COVID-19 is associated with the risk of cardiovascular disease death: A two-sample Mendelian randomization study - Miao, Jia-peng; Gu, Xiao-yu; Shi, Rui-zheng (Frontiers in Cardiovascular Medicine, 2022)
Objective: The aim of this study was to estimate causal effects of COVID-19 susceptibility and hospitalization on cardiac death using a two-sample MR (Mendelian randomization) analysis. Methods: We used statistics from a genome-wide association study (GWAS). We performed two-sample MR analysis using the inverse variance weighted (IVW) method. As sensitivity analyses, the MR-Egger regression, heterogeneity analyses and leave-one-out analysis were used. Reverse MR analyses was used to detect reverse causality. Statistical significance was defined as P < 0.05. Results: COVID-19 susceptibility may be a causal factor for cardiac death (β=2.188×10-3, P=0.002), and COVID-19 hospitalization also may be a causal factor for cardiac death (β=8.626×10-4, P=0.010). Sensitivity and reverse MR analysis suggested that no horizontal pleiotropy and reverse causality was found between COVID-19 and cardiac death. Conclusions: Our two-sample MR analysis suggested that there were causal effects of COVID-19 susceptibility and hospitalization on cardiac death using GWAS datasets.